Kontribusi forum anak daerah Kepahiang provinsi Bengkulu (FADEK) dalam perlindungan hak anak - Eka Aulia Rizki; Idi Warsah; Guntur Putra Jaya (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2020)
This study aimed to determine the contribution of Kepahiang Regional Children's Forum (FADEK) program in an effort to protect children's rights in that region. This study used a qualitative approach. The data were collected through observation, interviews and documentation. After the data were collected, they were further analyzed using Miles, Haberman, and Saldana’s model comprising the selection of data, presentation of data and drawing conclusions. This study found the conclusion that the establishment of this forum departed from Kepahiang youth’s concerns on the lack of parental care for children's rights, so this forum had the main mission to minimize the cases children experienced from both their surrounding people and other people. The contributions of this forum were: For the government, this forum made Kepahiang a city worthy of children by the Minister of Child and Women's Protection (PPA) in 2019. For the forum members, this forum trained them to become pioneers in struggling for their rights and peers’. For children, this forum provided assistance to children who were coping with the acts violating both customary law and the law on other criminal acts.